Improving the adhesion-to-fibers and film properties of corn starch by starch sulfo-itaconation for a better application in warp sizing. (June 2021) - Li, Wei; Zhang, Zhengqiao; Wu, Lanjuan; Zhu, Zhifeng; Xu, Zhenzhen
Abstract: The purpose of this work was to develop a new starch-based sizing agent [sulfo-itaconylated starch (SIS)] with high adhesion and film properties, through starch sulfo-itaconation containing itaconation of acid-hydrolyzed starch (AHS) with itaconic anhydride and subsequent sulfonation with NaHSO3 in aqueous medium. The granular SIS was characterized by Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) techniques. The adhesion of SIS to cotton fibers was evaluated by a standard method (FZ/T 15001–2008). And its film properties were also investigated in terms of tensile strength, breaking elongation, moisture regain, bending endurance and degree of crystallinity, etc. The experimental results showed that the SIS samples had higher adhesion to cotton fibers and lower film brittleness than AHS as a control. Increasing the level of starch sulfo-itaconation could gradually enhance bonding strength to cotton fibers, and increase breaking elongation and bending endurance of SIS film, indicating that increasing the number of sulfo-itaconate substituents could play a significantly positive role in overcoming the shortcomings (insufficient adhesion and brittle film) of starch. Considering the previous results, the granular SIS with a modification level range of 0.034–0.041 showed potential for the use as a new starch-based sizing agent in paper-making and textile industry. Highlights: Sulfoitaconylated starch (SIS) is successfully prepared by starch itaconation and subsequent sulfonation. SIS shows stronger adhesion to cotton fibers by contrast with AHS. SIS has better film properties such as breaking elongation and bending endurance than AHS. SIS can be used as a new bio-based starch sizing agent.